Characterisation of insulated Cu wire ball bonding - Leong, H.Y.; Yap, B.K.; Khan, N.; Ibrahim, M.R.; Tan, L.C.; Faiz, M. (Maney Publishing, 2014)
Insulated Cu wire technology offers potential solutions for fine and ultra-fine pitch wire bonding as the insulator coating on the bare wire prevents wires shorting problem. Most previous works focused on insulated wire stitch bonding. This paper presents a comparison study between insulated Cu and bare Cu wire ball-bonding process characterisation in the standpoints of free air ball formation, Al splash, hardness, ball bond strength and intermetallic growth at the bond interface study. Spherical and clean free air ball was formed using lower electric flame off energy compared to bare Cu wire. The study shows that insulated Cu bonding demonstrated comparable equivalent ball bond strength to bare Cu wire bonding at T-0 and even after subjected to isothermal aging 175 degrees C up to 1008 hours. Intermetallic formation was uniform at the bond interface for both wires. Insulated Cu wire demonstrates good bondability and reliability performance, suitable for fine pitch wire bonding in large-scale integration applications.